Nilai-nilai Pendidikan Islam dari Film Kartun Riko the Series: Tema tentang Puasa - Lestari, Atun; Nurjanah, Aswin; Ichsan, Yazida; Anendi, Yuhan; Mahmuda, Ibnu (Lembaga Yasin AlSys, 2023)
Fasting is an obligation for every Muslim who has fulfilled the requirements to do so, because fasting is the third pillar of Islam in Islam. The purpose of fasting is to make people fear Allah subhaanahu wa ta'ala. The research used is a literature study and in this article provides a review about fasting; understanding, various, arguments, virtues to threats for those who leave. This research was made with the aim that everyone, especially Muslims, can know and understand fasting in depth and more broadly.